Pollen Record of Humidity Changes in the Arid Western Qilian Mountains Over the Past 300 Years and Comparison With Tree-Ring Reconstructions - Wang, Jiale; Huang, Xiaozhong; Zhang, Jun; Xiang, Lixiong; Xiao, Yulin; Fontana, Luciane; Ren, Xiuxiu; Wang, Zongli (Frontiers in Earth Science, 2020)
In arid central Asia, the geo-ecological environment of the well-vegetated high mountains differs from that of the extensive arid Gobi desert areas, with the forested areas having experienced a different pattern of humidity variations compared to the dryland regions. Therefore, the moisture history of the forest areas reconstructed by tree rings may differ from that of the dryland areas. In the extremely arid area of the western Qilian Mountains and the surrounding dryland areas, where forest is absent, it is unclear how humidity conditions have changed over the past several centuries. Here, we use a pollen record from Tian’E Lake, with a chronology based on 210Pb and 137Cs, and with an average temporal resolution of ∼2 years, to reconstruct the humidity changes over the past 300 years. The results show that the pollen assemblage is dominated by Artemisia and Amaranthaceae (=Chenopodiaceae), and therefore, the A/C (Artemisia/Chenopodiaceae) ratio can be used to reconstruct changes in humidity conditions. Based on the pollen A/C ratio, two relatively wet periods are identified: ∼1740–1750 and 1840–1980, and two dry intervals: ∼1750–1840 and 1980–2018. This pattern of variation is similar to that reconstructed from nearby humidity records based on tree-ring width adjacent to the Tian’E Lake area and with instrumental records from meteorological stations over the past several decades. However, there are significantly different records between pollen-based and tree-ring based humidity during ∼1760–1830, 1880–1910, and 1920–2018 in the Qilian Mountains on long timescales. We conclude that pollen-based humidity records from dryland areas may differ from those reconstructed from tree-ring widths in forested mountain areas, especially when the temperature was increasing. It was further suggested that there was an antiphased relationship in humidity conditions between westerlies-dominated central Asia and monsoon areas over the past century.